Analysis of lower extremity proprioception for anterior cruciate ligament injury prevention: Current opinion - Nagai, T.; Schilaty, N. D.; Strauss, J. D.; Crowley, E. M.; Hewett, T. E. (Sports Medicine, 2018)
Lower extremity musculoskeletal injuries—such as ACL injury—are common, and the majority of those injuries occur without external player contact. In order to prevent non-contact musculoskeletal injuries, athletes must rely on accurate sensory information (such as visual, vestibular, and somatosensory) and stabilize joints during athletic tasks. Previously, proprioception tests (the senses of joint position, movement, tension or force) have been examined using static tests. Due to the role of proprioception in achievement of joint stability, it is essential to explore the development of dynamic proprioception tests. In this current opinion, the basic background on proprioception is covered, and the research gaps and future directions are discussed.